Knowledge, Awareness, and Attitudes about Research Ethics among Dental Faculty in the Middle East: A Pilot Study - Hadir F. El-Dessouky; Amr M. Abdel-Aziz; Chadi Ibrahim; Malini Moni; Reham Abul Fadl; Henry Silverman (International Journal of Dentistry)
Objective. To assess the knowledge, awareness, and attitudes of dental faculty regarding research ethics and research ethics committees (RECs). Design. Through convenience sampling, we distributed a survey to academics at dental faculties at two universities in the Middle East. We used descriptive, chi-square, and logistic regression statistics to analyze the data. Results. Our response rate was 62.5%. A large majority (>90%) held positive attitudes towards RECs; however, almost half (44.0%) thought that RECs would delay research. Less than half (36.8%) had received prior training in research ethics, and the average score they achieved on the questions on research ethics was only 40.2%. Most (>90%), however, were favorable towards research ethics education. Finally, some faculty held attitudes regarding certain research ethics practices that were not optimal. Conclusions. We conclude that among the dental faculties participating in our study, there is broad-based acceptance of RECs and training in research ethics, while there are knowledge gaps in research ethics. We recommend further studies to determine the generalizability of our findings to other institutions.